AN UPDATE OF THE JURASSIC OPHIOLITES AND ASSOCIATED CALC-ALKALINE ROCKS IN THE SOUTH APUSENI MOUNTAINS (WESTERN ROMANIA) - Bortolotti, Valerio; Marroni, Michele; Nicolae, Ionel; Pandolfi, Luca; Principi, Gianfranco; Saccani, Emilio (Ofioliti, 2004)
This paper presents a synthesis of the researches so far carried out by the authors on the Jurassic magmatic sequences of South Apuseni Mountains. The Apuseni Mountains represent an alpine orogenic belt located in the hinterland of the Southern Carpathians. The Apuseni Mountains include a pile of basement nappes affected by Hercynian metamorphism (Bihor, Biharia, Baia de Aries, Codru nappe complexes). These nappes are overlain by an imbricated stack of tectonic units mainly consisting of Late Cretaceous clastic deposits that are, in turn, topped by the Mures nappe. This nappe includes a Middle Jurassic ophiolite sequence covered by Upper Jurassic calc-alkaline volcanics. The ophiolite sequence consists of a gabbroic complex overlain by a sheeted dike complex and a volcanic sequence including massive and pillow-lavas. Cherts associated to pillow-lava basalts have provided Callovian to Oxfordian radiolarian associations. According to the geological and geochemical evidences, we propose that the ophiolite sequence preserved in the Southern Apuseni Mountains is representative of an oceanic lithosphere formed in a mid-ocean ridge setting. The calc-alkaline series is mostly characterized by volcanic rocks including: basalts, basaltic andesites, andesites, dacites and rhyolites showing geochemical features typical of an intra-oceanic arc setting, and is thought to be related to Late Jurassic convergence between Eurasia and Adria plate. The calc-alkaline series is in turn overlain by Late Jurassic shallow-water limestones showing a gradual transition to Cretaceous carbonate deposits. The geological and geochichemical features are consistent with a possible linkage of the Apuseni Mountains ophiolites with northern continuation of the Vardar oceanic domain of the Hellenic-Dinaric belt. The present-day location in the hinterland of the Carpathian area achieved in the Late Paleogene – Early Neogene time span, when the escape tectonics produced a large-scale displacement of blocks originated from the northernmost edge of the Adria plate.